Pengembangan Media Pembelajaran Articulate Storyline Menggunakan Model Think Pair Share di Kelas IV SDN Karang Tengah 07 - Magdalena, Ina; Fadillah, Yusuf; Maharani, Rani; Ariq, Muhammad; N, Gilang Kusuma (Lembaga Yasin AlSys, 2022)
This research is develop an Articulate Storyline learning media using Think Pair Share model was valid and practical. this research was Research and Development. The development procedure uses the ADDIE model consisting of analysis, design, development, implementation, and evaluation. the instrument used was a validity questionnaire and a practicality questionnaire. Data collection techniques used qualitative and quantitative techniques. The results of this study are in the form of learning media produced from the Articulate Storyline application which has an attractive appearance for elementary school students. Based on the results of media validator get 76.5% a very valid category. material validator get 91% a very valid category, linguists validator get 100% a very valid category. The practicality of the teacher's response at SDN Karang tengah 7 get 91.6% a very practical category and the practicality level at SDN Karang tengah 10 get 95.8% a very practical category. The practicality of the students' responses at SDN Karang tengah 7 get 91% a very practical category and the practicality level at SDN Karang tengah 10 get 93.8% a very practical category. It can be concluded that the Articulate Storyline learning media is valid and practical.